THE IMPACT OF VARIOUS INDIAN MEDICINAL PLANTS AS A WOUNDS HEALER - Srivastava Prabhat Kumar; Srivastava Smriti; Singh Anil Kumar; Dwivedi K. N. (International Journal of Ayurveda and Pharma Research, 2015)
Many requirements of human beings are fulfilled by the plants. They also prevent and cure various diseases of human beings including wounds and ulcers. Plants and their extracts have immense potential for the management and treatment of wounds. The management of wound has been a major problem since the early stages of medical science. In spite of brilliant progress of in surgery, wound management still remains a subject of speculation. The early manifestation of unsatisfactory wound healing gives rise to serious complications which can lead to prolonged healing and even death in surgical practice. These natural medicines for wound healing are cheap, affordable and purportedly safe as hyper sensitive reactions are rarely encountered with the use of these agents. These natural agents induce healing and regeneration of the lost tissue by multiple mechanisms. However, there is a need for scientific validation, standardization and safety evaluation of plants of the traditional medicine recommended for healing of the wounds.